Solve the equation. \[ (x+2)^{2 / 5}-5(x+2)^{1 / 5}+6=0 \] \( x=1 \) Simplify your answer. Type an integer or a sim
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To solve the equation \( (x+2)^{2/5} - 5(x+2)^{1/5} + 6 = 0 \), let's introduce a substitution. Let \( y = (x + 2)^{1/5} \). Then, \( y^2 = (x + 2)^{2/5} \), and we can rewrite the equation as: \[ y^2 - 5y + 6 = 0 \] This is a quadratic equation that can be factored: \[ (y - 2)(y - 3) = 0 \] So, the solutions for \( y \) are \( y = 2 \) and \( y = 3 \). Now, recalling our substitution \( y = (x + 2)^{1/5} \): 1. If \( y = 2 \): \[ (x + 2)^{1/5} = 2 \] Raising both sides to the fifth power gives: \[ x + 2 = 32 \implies x = 30 \] 2. If \( y = 3 \): \[ (x + 2)^{1/5} = 3 \] Raising both sides to the fifth power gives: \[ x + 2 = 243 \implies x = 241 \] Thus, the solutions are \( x = 30 \) and \( x = 241 \). To conclude, the simplified answer to the equation is \( 30 \) and \( 241 \).